2009
DOI: 10.4049/jimmunol.0901319
|View full text |Cite
|
Sign up to set email alerts
|

Binding of DC-HIL to Dermatophytic Fungi Induces Tyrosine Phosphorylation and Potentiates Antigen Presenting Cell Function

Abstract: APCs express receptors recognizing microbes and regulating immune responses by binding to corresponding ligands on immune cells. Having discovered a novel inhibitory pathway triggered by ligation of DC-HIL on APC to a heparin/heparan sulfate-like saccharide of syndecan-4 on activated T cells, we posited DC-HIL can recognize microbial pathogens in a similar manner. We showed soluble recombinant DC-HIL to bind the dermatophytes Trichophyton rubrum and Microsporum audouinii, but not several bacteria nor Candida a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 45 publications
1
39
0
1
Order By: Relevance
“…[18][19][20][21][22][23] Using FACS analysis, we found that IL-10-APC in contrast to moDC express higher levels of GITR, GITRL, syndecan-4 and PD-1. Furthermore, we were able to confirm our results obtained from the transcriptome analysis by showing that IL-10-APC express higher levels of osteoactivin, whereas PD-L1 was not upregulated (Fig.…”
Section: Il-10-apc Display Relevant Cell Intrinsic Differences Comparmentioning
confidence: 90%
See 1 more Smart Citation
“…[18][19][20][21][22][23] Using FACS analysis, we found that IL-10-APC in contrast to moDC express higher levels of GITR, GITRL, syndecan-4 and PD-1. Furthermore, we were able to confirm our results obtained from the transcriptome analysis by showing that IL-10-APC express higher levels of osteoactivin, whereas PD-L1 was not upregulated (Fig.…”
Section: Il-10-apc Display Relevant Cell Intrinsic Differences Comparmentioning
confidence: 90%
“…18,20,21 Osteoactivin differs from other inhibitory molecules since it is not only expressed on lymphoid, but also on non-lymphoid cells such as melanocytes, keratinocytes and osteoblasts and has an intracellular ITAM. [31][32][33] Cross-linking of the osteoactivin receptor with specific antibodies was shown to induce tyrosine phosphorylation of the ITAM 20,22 suggesting that activation of osteoactivin induces MDSC to express IFNg, nitric oxide and reactive oxygen species. 20 Mice lacking the osteoactivin/syndecan-4 pathway are characterized through a massive expansion of pathogenic T cells during experimental autoimmune encephalomyelitis 20 or following allogeneic bone marrow transplantation, an effect that might be mediated through a combination of hyperactive APC and disabled MDSC.…”
Section: Discussionmentioning
confidence: 99%
“…These mice exhibit autoimmune pigmentary glaucoma and compromising ocular immunosuppression, which is manifested by deficient anterior chamberassociated immune deviation (18,46). In the context of innate immunity, Gpnmb was demonstrated to be involved in recognition of dermatophytic fungi (24). Overexpression of Gpnmb dampens LPS responses, suggesting that Gpnmb negatively regulates inflammatory macrophage responses (17).…”
Section: Discussionmentioning
confidence: 99%
“…It is also referred to as osteoactivin, hematopoietic growth factor-inducible neurokinin 1, and the dendritic cell-associated heparin sulfate proteoglycan-dependent integrin ligand (18)(19)(20)(21). Gpnmb has been implicated in regulation of both adaptive and innate immunity (22)(23)(24). Interestingly, Gpnmb induction has also been observed in a mouse model of Gaucher disease, a macrophage lipid-storage disease characterized by deficient lysosomal acid b-glucosidase and IR in humans (25,26).…”
mentioning
confidence: 99%
“…It was shown previously that pathogenic ascomycetes, including dermatophytes, bind to DCs via the C-type lectin DC-SIGN (dendritic cell-specific intercellular adhesion molecule 3-grabbing nonintegrin) (12,30). A novel pattern recognition pathway to detect dermatophytes via binding to DC-HIL (dendritic cell-associated heparan sulfate proteoglycan-integrin ligand) (31) and the subsequent phosphorylation of an ITAM (immunoreceptor tyrosine-based activation motif) was suggested previously (11). Since binding and phosphorylation have been observed for Trichophyton rubrum but not for Candida albicans, it is conceivable that this mechanism is specific to dermatophytes.…”
Section: Discussionmentioning
confidence: 99%